Pengaruh Penerapan Model Guided Discovery Learning Metode Concept Maps dan Mind Maps terhadap Penguasaan Konsep Biologi Siswa SMA - Asyhuri, Ahadia Busyaroh; Maridi, Maridi; Santosa, Slamet (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The research aims to know the biology concepts mastery difference between guided discovery learning with concept maps and mind maps in senior high school students. The type of this research is quasy experimental research using pos-test only only nonequivalent control group design. The population were students grade X of SMA N 1 Boyolali academic year 2016/2017. The sampel were X MIA 4 (using guided discovery learning with concept maps), X MIA 5 (using guided discovery learning with mind maps), and X MIA 6 (using guided discovery learning), selected through claster random sampling. Post-test data was analyzed with one way Anova test, followed with comparison test of Tukey’s method (with level of significance 0.05), make used of Statistical Product and Service Solution (SPSS) 23.0. The result showed that there were biology concepts mastery difference between implementation of guided discovery learning with concept maps method and mind maps method in students grade X of SMA N 1 Boyolali academic year 2016/2017. The biology concepts mastery of guided discovery learning with concept maps method increase five of seven indicators of concept mastery. There are know the feature of a concept, know characteristic of a concept, know and use concept correlation, and apply a concept to solve problem. Guided discovery learning with mind maps methode work up to select example or not of a concept, and recognize a concept in different case.